2004
DOI: 10.1007/s10067-004-0902-y
|View full text |Cite
|
Sign up to set email alerts
|

Oral enzyme combination versus diclofenac in the treatment of osteoarthritis of the knee ? a double-blind prospective randomized study

Abstract: The aim of this study was to compare the efficacy and safety of an oral enzyme-rutosid combination (ERC) containing rutosid and the enzymes bromelain and trypsin, with that of diclofenac in patients with osteoarthritis (OA) of the knee. A total of 103 patients presenting with painful episodes of OA of the knee were treated for 6 weeks in two study centers in a randomized, double-blind, parallel group trial. Altogether, 52 patients were treated in the ERC group and 51 patients were treated in the diclofenac gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
1
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 11 publications
0
39
1
3
Order By: Relevance
“…These include the experimental allergic encephalomyelitis (EAE) model of the human autoimmune disease multiple sclerosis (3), carrageenan-induced pleurisy in the rat (4)(5)(6), immunologically mediated arteriosclerosis in rat aortic allografts (7), rheumatologic diseases in mice and humans (8)(9)(10)(11)(12)(13), and allergic asthma (14) and rhinitis (15). Some studies demonstrated that bromelain had efficacy similar to standard anti-inflammatory drugs such as dexamethasone (5,6) or non-steroidal anti-inflammatory agents (NSAIDs) (8,10,11,16). Our previous studies showed that oral administration of 5 mg bromelain/day markedly decreased the development and severity of inflammatory bowel disease in IL-10 −/− mice (17).…”
Section: Introductionmentioning
confidence: 99%
“…These include the experimental allergic encephalomyelitis (EAE) model of the human autoimmune disease multiple sclerosis (3), carrageenan-induced pleurisy in the rat (4)(5)(6), immunologically mediated arteriosclerosis in rat aortic allografts (7), rheumatologic diseases in mice and humans (8)(9)(10)(11)(12)(13), and allergic asthma (14) and rhinitis (15). Some studies demonstrated that bromelain had efficacy similar to standard anti-inflammatory drugs such as dexamethasone (5,6) or non-steroidal anti-inflammatory agents (NSAIDs) (8,10,11,16). Our previous studies showed that oral administration of 5 mg bromelain/day markedly decreased the development and severity of inflammatory bowel disease in IL-10 −/− mice (17).…”
Section: Introductionmentioning
confidence: 99%
“…In a clinical study conducted in 2004, the efficacy of an enzyme-flavonoid mixture was compared with diclofenac, a prescription NSAID 28 .The proteolytic enzymes used were bromelain and trypsin. These three agents were used in the form of an enteric-coated tablet (to prevent the enzymes from being destroyed by stomach acid) that contained 90 mg of bromelain, 48 mg of trypsin, and 100 mg of rutoside.…”
Section: Combination Of Trypsin Rutoside and Bromelainmentioning
confidence: 99%
“…Bromelain u kombinaciji sa tripsinom i rutozidom, primenjen kod pacijenata (n = 52) sa osteoartiritisom kolena u toku šest nedelja. potvrdio je svoj analgetički efekat i bio je podjednako efikasan kao i diklofenak (n = 51) (30). u svim studijama pacijenti su prema sopstvenoj proceni "dobro", odnosno "vrlo dobro" podnosili bromelain, a u studiji tilwe i saradnika (29) čak i dnevnu dozu bromelaina od oko 1890 mg u obliku Phlogenzyma ® .…”
unclassified